Investasi Asing Langsung, Perdagangan Internasional, dan Kualitas Lingkungan di Indonesia - Hanifah, Azimah; Sutrisno, Bambang; Hindasah, Lela; Riyanti, Riyanti; Herliyana, Dea (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This paper investigates the influence of foreign direct investment and international trade on environmental quality in Indonesia from 1990 to 2018. Environmental quality is measured by carbon dioxide emissions. The estimation method employed is autoregressive distributed lag. This study finds that foreign direct investment positively affects carbon dioxide emissions in the short term but has no impact in the long term. International trade positively affects carbon dioxide emissions in the short and long terms. The results recommend policymakers in Indonesia control carbon dioxide emissions from foreign direct investment projects and export and import activities.